Authority of Second-Tier Governments to Reduce Deforestation in 30 Tropical Countries - Busch, Jonah; Amarjargal, Oyut (Frontiers in Forests and Global Change, 2020)
The authority of state- and province-level governments (“second-tier governments”) to make decisions related to slowing deforestation independently of national governments varies widely across countries. Here we systematically catalog whether second-tier governments in 30 tropical countries with high projected future emissions from deforestation possess 14 distinct types of general and forest-related authority. We compile this information in a free, open-access database. Second-tier governments have broadest authority to reduce deforestation in India, Brazil, Indonesia, Malaysia, Papua New Guinea, Peru, China, Laos, Mozambique, and Vietnam. Second-tier governments have the least authority in Central African Republic, Gabon, Angola, Madagascar, Bolivia, Cambodia, Cameroon, Guyana, Suriname, Thailand, and Venezuela. Second-tier governments have intermediate authority in Democratic Republic of Congo, Ecuador, Mexico, the Philippines, Colombia, Myanmar, Tanzania, Zambia, Mexico, and Republic of Congo. Authorities that second-tier governments most commonly possess include development planning, taxation, budgeting, and roads. Authorities that second-tier governments least commonly possess include land ownership, police, permits for mining, Indigenous affairs, and protected areas. Authorities possessed by an intermediate number of second-tier governments include spatial planning, elections, courts, and permits for agriculture. More than one-quarter of future emissions from deforestation between 2020-2050 is projected to come from just seven out of 678 second-tier jurisdictions: Amazonas, Pará, and Mato Grosso (Brazil), Équateur and Orientale (Democratic Republic of Congo), Loreto (Peru), and El Beni (Bolivia). After weighting for authority, our list of the 50 second-tier jurisdictions in the tropics that are the highest priority for reducing emissions from deforestation shifts to include fewer second-tier jurisdictions in Africa (where second-tier governments have 4.2 authorities out of 14 in the average country) and Latin America (6.3 authorities out of 14) and more second-tier jurisdictions in Asia (8.5 authorities out of 14). Second-tier jurisdictions that have formally expressed interest in reducing emissions from deforestation, e.g. through the Governors’ Climate and Forest Task Force, Under2 Coalition, or New York Declaration on Forests, possess greater authority to reduce deforestation on average than other jurisdictions. Information on second-tier governmental authority, when complemented with deeper country-specific knowledge, can help initiatives for reducing emissions from deforestation (REDD+) prioritize support across regions and across sectoral interventions.